KRITIK SOSIAL DAN POLITIK DALAM KIDUNG PENGILING KARYA KIAI IMAM MALIK - Miftakhur Ridlo (UIN Sayyid Ali Rahmatullah Tulungagung, 2019)
Kidung Pangiling is a Javanese Poetry that written by Kiai Imam Malik in Losari, Mojokerto. He is a founder of hermitage “Mayangkoro Pondok Pesantren Sambung Sari Noto Projo Majapahit Bangkit Nusantara Jaya”. Kiai Imam Malik has written Kidung Pengiling aimed at giving advice and reminders to the community during the 1997 - 2006. The social aspects in Kidung Pangiling by Kiai Imam Malik broadly explain the social phenomena that occur in society. This social phenomenon has become a habit and tradition that deviates from the concept of religion and public norms. The political aspect in Kidung Pangiling by Kiai Imam Malik contains criticism of the New Order government in 1998 and political phenomena related to deviant state officials' behavior such as corruption, collusion and nepotism. It is also criticized several parties whose ways were not for public interests. Keywords: Kidung Pangiling, Political Critique, Social Critique